1987
DOI: 10.1128/jvi.61.3.764-773.1987
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus gene expression: control mechanisms at early and late times of infection and nuclear-cytoplasmic transport of virus-specific RNAs

Abstract: Single-stranded M13 DNAs specific for various influenza virus genomic segments were used to analyze the synthesis of virus-specific RNAs in infected cells. The results show that influenza virus infection is divided into two distinct phases. During the early phase, the syntheses of specific virion RNAs, viral mRNAs, and viral proteins were coupled. Thus, the NS (nonstructural) virion RNA was preferentially synthesized early, leading to the preferential synthesis of NS1 viral mRNA and NS1 protein; in contrast, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(75 citation statements)
references
References 40 publications
7
68
0
Order By: Relevance
“…182,184,206 In contrast, HA, NA, and M1 mRNAs are preferentially expressed. 182,184,206 In general, most of the capped and polyadenylated viral mRNAs would be transported from the nucleus to the cytoplasm for protein synthesis. On the other hand, the membrane-bounded proteins, such as HA, NA, and M2, would pass the secretory pathway at the trans-Golgi network for protein maturation.…”
Section: Expression Of Influenza Viral Proteinsmentioning
confidence: 99%
See 3 more Smart Citations
“…182,184,206 In contrast, HA, NA, and M1 mRNAs are preferentially expressed. 182,184,206 In general, most of the capped and polyadenylated viral mRNAs would be transported from the nucleus to the cytoplasm for protein synthesis. On the other hand, the membrane-bounded proteins, such as HA, NA, and M2, would pass the secretory pathway at the trans-Golgi network for protein maturation.…”
Section: Expression Of Influenza Viral Proteinsmentioning
confidence: 99%
“…183 In addition, cRNA is not polyadenylated. Although both cellular and viral factors have been suggested to have crucial roles in the transcription-replication regulation, 99,184,204,205 the mechanism for the switching from transcription to replication is still poorly understood. Recently, Vreede et al 101 demonstrated that there may be no switch regulating the initiation of RNA synthesis and proposed a model suggesting that nascent cRNA is degraded by host cell nucleases unless it is stabilized by newly synthesized viral RNA polymerase and NP proteins.…”
Section: Viral Replication Of Influenza Virusmentioning
confidence: 99%
See 2 more Smart Citations
“…Influenza virus will infect a number of mammalian cell lines such as MDBK, baby hamster kidney (BHK-21, CCL #lo; ATCC), MDCK, or monkey kidney (African Green monkey kidney, CV-1, CCL #70; ATCC). The time course of viral polypeptide synthesis depends on the strain of virus and the host cell, as well as on the multiplicity of infection (Skehel, 1972;Meier-Ewert and Compans, 1974;Lamb and Choppin, 1976;Shapiro et al, 1987). Thus, it is important to establish the growth properties and time course of replication of a given influenza virus strain in the cell type of interest before planning specific experiments.…”
Section: Influenza Virus Polypeptide Synthesismentioning
confidence: 99%